Effectiveness of an educational strategy in increasing the prescription of adequate thromboprophylaxis in the internal medicine service of general hospital - Vásquez Kunze , Sergio (2024)
Objective: To determine whether an educational intervention strategy would improve the frequency of medical prescriptions for adequate thromboprophylaxis in a medicine service. Methods: Quasi-experimental study, in which in the pre-intervention phase the frequencies of indication of appropriate thromboprophylaxis by physicians from the medicine service were obtained. An 8-week educational intervention was carried out with this same group of doctors. In the post-intervention phase, the frequency of adequate thromboprophylaxis was measured at 2 and 4 months after the intervention. Results: The educational intervention was implemented in 112 resident physicians in medicine specialties. All prescriptions were made by the first-year resident physicians and endorsed by their supervising physician. Prior to the intervention, 47 (44.35%) adequate prescriptions were obtained, 13 (12.26%) suboptimal, 4 (3.77%) inadequate, and 42 (39, 62%) no prescription. After the intervention, the following 2 months were obtained: 78 (75.72%) adequate prescriptions, 7 (6.79%) suboptimal, 4 (2.91%) inadequate and 15 (14.58%) no prescriptions, there being a significant difference with the baseline level. At the subsequent 4 months post-intervention, the following were obtained: 86 (83.49%) adequate, 5 (4.85%) suboptimal, 2 (1.94%) inadequate and 10 (9.72%) no prescription, with a difference significant with the baseline level. There was no increase in the frequency of overuse. Conclusions: The application of an educational strategy to medical personnel was effective in increasing correctly indicated thromboprophylaxis prescriptions in a medical service. No overuse of thromboprophylaxis was found after the intervention.